Didactic aspects of reading mathematical texts - Sičiūnienė, Viktorija (Lietuvos matematikos rinkinys, 2015)
The article deals with the problem of developing reading skills in mathematics classes. The author presents a modern approach to the concept of competence to read and proposes a model of empirically tested reading strategies. The results of testing the ability of reading strategies application by 5–6 form students are provided and recommendations for the improvement of teaching the reading strategies in subject classes are offered.
Keywords: reading competence; reading strategies; reading skills in mathematics classes